STRATEGI PEMERINTAH DALAM PENINGKATAN KUALITAS SUMBER DAYA MANUSIA PADA GENERASI MUDA DESA COMPONG - Ana Satria Syahda; Ahmad Yasin; Barisan Barisan; Buhari Buhari; Muh Tamrin (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine the Government's Strategy in Improving the Quality of Human Resources in the Young Generation of Compong Village, Pitu Riase District, Sidenreng Rappang Regency by using qualitative descriptive research and using data collection techniques, namely interviews, observations, and documents. The results showed that the strategy carried out by the government, especially in the village of Compong, was still lacking in terms of increasing human resources, especially for the younger generation in the village. There are still many young people in the village of Compong who need more support from village government officials, especially from the village head himself. The village head must play an important role in improving the quality of the younger generation, the younger generation cannot develop if the village officials, especially the village head, have not been able to master the things that are important for the young generation in the village of Compong. There are many ways that can be done or used as a strategy for the village government if the village apparatus is able to explore what is the obstacle for the younger generation so that they have not been able to help the village apparatus in improving the good name of the village.